Ultrasound-Guided Needle Aspiration of an Iliac Crest Abscess in a Pediatric Emergency Department. Issue 3 (March 2020) - Surdhar, Ian; Kirschner, David
Abstract : Abstract: Point-of-care ultrasound (POCUS) is an integral part of pediatric emergency medicine. One evolving use of POCUS is in the diagnosis and management of skin and soft tissue infections. Point-of-care ultrasound can be used to identify clinically occult infections and can be used to guide percutaneous drainage of both superficial and deep abscesses. Here, we present a case where POCUS- and US-guided needle aspiration had a significant impact on patient care by providing rapid diagnosis, as well as expediting microbiological speciation in a young male presenting with left-sided back and buttock pain.